Searchable database of climate-related journal articles published between 2012 to 2023 from across all CGIAR centres unveiled - Bosire, Caroline; Orth, Alan S.; Muhammad, Yasir; Mukherji, Aditi (CGIAR System Organization, 2024)
The CGIAR Climate Impact Platform, in partnership with the CGSpace team at the International Livestock Research Institute (ILRI), has developed a database of 3,466 climate-related journal articles authored by CGIAR scientists from 2012 to 2023. This collaboration aims to address the fragmentation of climate-related research across CGIAR centres and promote knowledge sharing and collaboration. A Power BI dashboard has been created for the database, enabling users to explore the research interactively, create visualisations of CGIAR climate research tailored for different audiences and provide quantitative representation of the research in reports and other outputs.